Contemporary diagnosis and management of severe tricuspid regurgitation. Issue 4 (10th September 2022) - Zahr, Firas; Chadderdon, Scott; Song, Howard; Sako, Edward; Fuss, Cristina; Bailey, Steven R.; Cigarroa, Joaquin
Abstract: Many novel percutaneous interventions are being developed for application in the tricuspid valve position. At the present time in the United States, there are no commercially available transcathter devices for this application. This article reviews the growing evidence for diagnosing, imaging, and treating severe tricuspid regurgitation as well as the surgical and transcatheter options that are under current development and in various stages of clinical trials.